Zen and the Art of Academic Maintenance - Curry, Stephen (Septentrio Conference Series, 2016)
Watch the VIDEO of the presentation. Robert Pirsig’s book, Zen and the Art of Motorcycle Maintenance, which is an exploration of the metaphysics of quality, is a Guinness world record holder. No best-seller has been rejected by more publishers – 121 in all. That numerical anomaly, mentioned at the top of the Wikipedia entry for the book (because of our obsession with quantity and rank), reminds us that identifying quality is hard. It requires expertise, but also the imagination to anticipate the future consequences of any new work – whether it be a book or a research paper. Time and again in academia, we get such judgments wrong. And yet, our systems of incentive and reward are increasingly tightly geared to the moment and place of publication. The evaluation of the work itself, or of the idea that it is a living thing that reaches out into the world, is being undermined as busy researchers strive to please busy masters who turn too often to numbers to make their assessment. Quantity is the pernicious proxy that trumps quality. But we must rediscover quality, in all its dimensions, if we are to maintain the reputation of the academy for unflinching interrogation. And one of the most important of those dimensions is openness, which can serve not only as a buttress for quality, but also as a reminder to the academy that freedom of inquiry brings responsibilities to society that can also be enriching.